Dashboard to monitor outages in a smart grid - Laureano, Raul M. S.; Laureano, L.; Andreia C. P. Sanz (2020 15th Iberian Conference on Information Systems and Technologies (CISTI), 2020)
With the appearance of smart grid and smart meters, the need to create technological solutions that allow energy distributors to monitor events and communicate with meters installed in the smart grid, has been increasing. Considering the above, and to help the events monitoring and the communications in the grid, specifically the power failures, this research has as main objective to build a dashboard to monitor outages in a smart grid. For this purpose, a specialized company in the electrical sector was selected to apply and validate the dashboard. The CRISP-DM methodology was adopted, and it is focused on the business and require systematic interaction with business experts. Based on the literature about performance indicators in the electrical sector and dashboard's, and considering several interviews conducted with a specialist, metrics and performance indicators were defined. The graphics to include in the dashboard which are appropriate to the objectives and to the problem have also been defined. To evaluate the dashboard's usefulness and usability, a questionnaire was drawn up and then applied to a specialist in this area. It was possible to conclude that the tactical dashboard, with monthly and weekly views, is useful and easy to use. Thus, with this investigation, the companies win a dashboard to be incorporated into their commercial solutions and to be used by their customers. In addition, this dashboard presents a set of indicators to be monitored in the sector of energy distribution and demonstrates the suitability of the CRISP-DM methodology for the creation of dashboard's.